2021
DOI: 10.1155/2021/6301433
|View full text |Cite
|
Sign up to set email alerts
|

Role of Exosomal MicroRNAs and Their Crosstalk with Oxidative Stress in the Pathogenesis of Osteoporosis

Abstract: Osteoporosis (OP) is an aging-related disease involving permanent bone tissue atrophy. Most patients with OP show high levels of oxidative stress (OS), which destroys the microstructure of bone tissue and promotes disease progression. Exosomes (exos) help in the delivery of microRNAs (miRNAs) and allow intercellular communication. In OP, exosomal miRNAs modulate several physiological processes, including the OS response. In the present review, we aim to describe how exosomal miRNAs and OS contribute to OP. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 98 publications
0
10
0
Order By: Relevance
“…The disease is related to an imbalance between the number and function of osteoblasts and osteoclasts. Moreover, angiogenesis, inflammation, oxidative stress and miRNAs have been involved in the process of osteoporosis (Li et al, 2018;Lu et al, 2021). It was reported that MSC-Exos could promote osteogenesis of BMSCs and promote the proliferation of osteoblasts to alleviate osteoporosis (Qi et al, 2016;Zhao et al, 2018).…”
Section: Improving Osteoporosismentioning
confidence: 99%
“…The disease is related to an imbalance between the number and function of osteoblasts and osteoclasts. Moreover, angiogenesis, inflammation, oxidative stress and miRNAs have been involved in the process of osteoporosis (Li et al, 2018;Lu et al, 2021). It was reported that MSC-Exos could promote osteogenesis of BMSCs and promote the proliferation of osteoblasts to alleviate osteoporosis (Qi et al, 2016;Zhao et al, 2018).…”
Section: Improving Osteoporosismentioning
confidence: 99%
“…In recent years, osteoporosis has become a serious healthcare concern for the aging population [ 20 , 21 ]. It is projected that more than about 50% of all osteoporotic hip fractures will occur in Asia by the year 2050.…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes carry nucleic acids, proteins, lipids, and metabolites that can target receptor cells to be taken up through membrane fusion or endocytosis. In addition, exosomes can cross barriers, such as the blood-brain barrier, which makes them natural vectors in vivo ( Ha et al., 2016 ; Lu et al., 2021 ). Recently, exosomes have been utilized as non-viral vectors for RNA delivery, which indicates their high biocompatibility, low clearance, and suitability for targeting cells ( Duan et al., 2021 ).…”
Section: Ncrna Delivery Scaffolds For Bone Defect Therapymentioning
confidence: 99%